Non activated protein C supplementation in septic pediatric hematological patients - Teresa Perillo; Paola Muggeo; Giampaolo Arcamone; Francesco De Leonardis; Nicola Santoro (MDPI AG, 2016)
The purpose of the study was to examine safety and efficacy of non-activated Protein C (PC) supplementation in our cohort of septic pediatric hematological patients. We conducted a retrospective study of 22 septic patients receiving human plasma-derived PC concentrate from 2008 to 2015 at our Pediatric Oncology Center (Bari, Italy). The Surviving sepsis campaign definitions for sepsis, severe sepsis and septic shock were used to define the patients' septic status. For each patient, we calculated Lansky performance status scale (LPSS) and a risk score defined the Hematologic risk score (HRS) that we created in 2007. Patients were defined as High risk for severe sepsis/septic shock in case of HRS>3. HRS10% PC concentration decrease within 12 hours from the first evaluation. All patients received 80 U/kg/day PC, intravenously, every twenty-four hours. No drug-related adverse event was observed. The observed sepsis-related mortality rate in our cohort was 9%. PC supplementation in our cohort appeared to be safe, and, probably due to prompt PC administration, we observed an overall mortality that was much lower than expected mortality in cancer severe septic patients.